RICE RESILIENCE IN THE FACE OF CLIMATE CHALLENGES EXPLORING DROUGHT RESPONSE IN RICE GENOTYPES - AYUB, MA; IJAZ, M; BANO, M; BIBI, T; GULNAZ, S; KHAN, RAR; MALLHI, AR; SARFRAZ, S; AHSAN, A; ANWAR, MR; LATIF, A; NAZAR, MZK; et al. (Biological and Clinical Sciences Research Journal, 2023)
Climate change is posing significant challenges to agriculture, threatening global food security. Among these challenges, drought stress is a formidable obstacle to rice production, a staple food for billions. Drought stress disrupts vital physiological processes, causing yield losses and impacting grain quality. Developing drought-tolerant rice varieties is essential to ensure food production and farmers' livelihoods. This study explores the drought tolerance potential of six Basmati rice genotypes: Basmati 198 (G1), Basmati 385 (G2), Rachna basmati (G3), Super Basmati (G4), Shaheen basmati (G5), and Basmat 2000 (G6). These genotypes have previously demonstrated submergence tolerance. By subjecting them to drought stress, we aim to assess their adaptability to multiple stressors, crucial in changing climates. A Randomized Complete Block Design was employed, ensuring methodological rigor. Seedlings were transplanted into the field, and drought stress was induced during the booting stage. We monitored various traits, including plant height, productive tillers, panicle length, spikelet numbers, fertility, branches, biological yield, grain yield, and harvest index. Statistical analyses revealed significant genotype-specific responses to drought. Results showed significant differences among genotypes under both control and drought conditions, underscoring genetic variability. Drought stress significantly impacted most traits. Basmat 2000 (G6) demonstrated superior performance under drought conditions. Clustering analysis revealed genetic diversity among genotypes, offering insights for breeding programs. Correlation analysis highlighted the importance of specific traits for grain yield. In conclusion, this study contributes to understanding genetic diversity among Basmati rice genotypes under drought stress. The findings emphasize the need for developing drought-tolerant rice varieties and offer valuable insights for sustainable rice cultivation in changing climates.